Factor Structure and Psychometric Properties of the Peritraumatic and Posttraumatic Emotions Questionnaires Among Active Duty Military Personnel With Posttraumatic Stress Disorder. Issue 6 (12th December 2018) - Zang, Yinying; Gay, Natalie G.; Kaczkurkin, Antonia N.; McLean, Carmen P.; Wachen, Jennifer Schuster; Yarvis, Jeffrey S.; Litz, Brett T.; Yadin, Elna; Mintz, Jim; Roache, John D.; Young‐McCaughan, Stacey; Peterson, Alan L.; et al.
Abstract: The Peritraumatic Emotions Questionnaire (Peri‐TEQ) and Posttraumatic Emotions Questionnaire (Post‐TEQ) are self‐report measures of emotions experienced during and after a traumatic event, respectively. The factor structure and psychometric properties of the Peri‐ and Post‐TEQ were investigated among 474 military personnel with posttraumatic stress disorder (PTSD) following deployment. Exploratory factor analysis and confirmatory factor analysis were conducted to test the factor structure of the scales. Internal consistency, composite reliability, convergent validity, and discriminant validity were also assessed. Four factors were identified for the Peri‐TEQ (Fear, Humiliation, Anger, and Sadness), and three factors were identified for the Post‐TEQ (Fear, Anger‐Hurt, and Humiliation). The full scales and all subscales demonstrated adequate‐to‐good internal consistency, Cronbach's αs = .722–.893. The subscales demonstrated adequate‐to‐good composite reliability, Cronbach's αs = .763–.861. The Peri‐ and Post‐TEQ demonstrated good convergent validity with measures of PTSD symptoms, r s = .229–.601, p s < .001, and depressive symptoms, r s = .284–.470, p s < .001, and good discriminate validity with measures of resilience, p s = .116–.940, and unit cohesion, Peri‐TEQ, p = .304 and Post‐TEQ, r = −.123, p = .008. The Humiliation subscales demonstrated good convergent validity with guilt cognitions, r s = .315–.341, p s < .001, and the Anger subscales demonstrated good convergent validity with state anger, r s = .260–.347, p s < .001. The Peri‐ and Post‐TEQ are reliable, valid self‐report measures of emotions during and in response to remembering a trauma. The results support the use of these measures in research investigating trauma‐related emotions.